2021
DOI: 10.3389/fphys.2021.734038
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Physical Exercise Activates ATR2 Receptors, Improving Inflammation and Oxidative Stress in the Duodenum of 2K1C Hypertensive Rats

Abstract: Background: In addition to the cardiovascular and renal systems, the gastrointestinal tract also contains angiotensin ATR1a, ATR1b, and ATR2. We previously observed that the 2Kidney-1Clip hypertension model elicits physical exercise and gastrointestinal dysmotility, which is prevented by renin-angiotensin system blockers. Here, we investigate the effect of physical exercise on inflammation, stress biomarkers, and angiotensin II receptors in the duodenum of 2K1C rats.Methods: Arterial hypertension was induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Ang II activates both receptors in the smooth muscle cells but also presynaptic receptors in other cells crucial for colonic function, an intricate network that has been reported to be altered in the diseased colon [ 27 , 29 , 54 ]. Regarding Ang II-mediated effects, it is known that contractile responses in intestinal smooth muscle occur mainly through the activation of AT 1 R, while AT 2 R’s role according to our group and others, seems to be more important under pathological conditions [ 27 , 55 , 56 ]. Not surprisingly, we observed that the AT 1 R antagonist (candesartan, 10 nM) completely abolished AngII-mediated contractile response in the ileum and all colon segments of both control and diabetic animals.…”
Section: Discussionmentioning
confidence: 82%
“…Ang II activates both receptors in the smooth muscle cells but also presynaptic receptors in other cells crucial for colonic function, an intricate network that has been reported to be altered in the diseased colon [ 27 , 29 , 54 ]. Regarding Ang II-mediated effects, it is known that contractile responses in intestinal smooth muscle occur mainly through the activation of AT 1 R, while AT 2 R’s role according to our group and others, seems to be more important under pathological conditions [ 27 , 55 , 56 ]. Not surprisingly, we observed that the AT 1 R antagonist (candesartan, 10 nM) completely abolished AngII-mediated contractile response in the ileum and all colon segments of both control and diabetic animals.…”
Section: Discussionmentioning
confidence: 82%
“…However, the role of hypertension on inflammation and oxidative stress affecting the GI tract still lacks consistent experimental evidence. Our research group was pioneering to show increases in pro-inflammatory cytokines and pro-oxidant markers in the duodenum of rats with 2K1C-induced hypertension ( 12 ). Here, we aimed at further characterizing the alterations of oxidative/nitrosative stress and inflammatory biomarkers in the gastric fundus, duodenum, and colon of SHR rats, which might have a functional impact on GI motility, namely on solid GE.…”
Section: Discussionmentioning
confidence: 99%
“…MPO activity in the resuspended pellet was evaluated by measuring the change in absorbance at 450 nm using o-dianisidine dihydrochloride and 1% hydrogen peroxide. The results are reported as units of MPO per mg of tissue (UMPO/mg of tissue) ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations